2022
DOI: 10.3390/met12091535
|View full text |Cite
|
Sign up to set email alerts
|

Features of Changes in the Surface Structure and Phase Composition of the of α + β Titanium Alloy after Electromechanical and Thermal Treatment

Abstract: Changes of structure, phase composition and microhardness in high-strength α + β titanium alloy were investigated after electromechanical treatment (EMT) and subsequent aging. The EMT was performed with alternating current density (j of 300 and 600 A/mm2). The aging was performed upon heating at 600 °C and exposure for 14 h. Methods of scanning electron microscopy, X-ray phase structure, micro X-ray spectral and durometric analyses were used. Modified layers (up to 200–250 µm in depth) on the surface of α + β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…Silicon (Si), which can be found as silicide and solid solution, is a crucial element in titanium (Ti) alloys. Some studies have demonstrated that the addition of silicon to titanium alloys can improve strength, creep resistance and oxidation resistance, as well as reduce fluidity, particularly at ambient temperature [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon (Si), which can be found as silicide and solid solution, is a crucial element in titanium (Ti) alloys. Some studies have demonstrated that the addition of silicon to titanium alloys can improve strength, creep resistance and oxidation resistance, as well as reduce fluidity, particularly at ambient temperature [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…атематические модели тепловых процессов комбинированных методов электромеханической обработки (ЭМО) с точки зрения металловедения имеют наибольшее сходство с термомеханической обработкой металлов [1][2][3][4][5][6] и основываются на уравнении теплопроводности. При этом учитываются отличия теплофизических свойств (температуропроводности ω, теплоемкости k, теплопроводности λ и теплоотдачи α), которые ограничиваются начальными и граничными условиями, технологическими и другими особенностями исследуемых методов обработки.…”
Section: Introductionunclassified